A randomized, double-blind, placebo-controlled study to assess the efficacy and safety of cinacalcet in pediatric patients with chronic kidney disease and secondary hyperparathyroidism receiving dialysis - Warady, Bradley A.; Schaefer, Franz (Pediatric nephrology, 2019)
BACKGROUND: This randomized phase 3 study evaluated the efficacy and safety of cinacalcet in children with secondary hyperparathyroidism (SHPT) receiving dialysis. - METHODS: This study had double-blind and open-label phases. Eligible patients aged 6-< 18 years were randomized to cinacalcet (starting dose ≤ 0.20 mg/kg) or placebo. The primary endpoint was ≥ 30% reduction from baseline in mean intact parathyroid hormone (iPTH). Secondary endpoints included mean iPTH ≤ 300 pg/mL; percentage change from baseline in corrected total serum calcium, phosphorus, and calcium phosphorus product (Ca × P); and safety. - RESULTS: The double-blind phase comprised 43 patients (cinacalcet, n = 22; placebo, n = 21). Nineteen months into the study, regulatory authorities were notified of a fatality; the study was subsequently terminated after a 14-month clinical hold. Before the hold, 12 patients (55%) on cinacalcet and four (19%) on placebo achieved the primary endpoint (p = 0.017), and 27% and 24%, respectively, achieved iPTH ≤ 300 pg/mL. The between-group differences (95% CI) in percentage changes for total serum calcium, phosphorus, and Ca × P were - 4% (- 9 to 1%), - 6% (- 21 to 8%), and - 10% (- 23 to 3%). The mean maximum actual weight-adjusted daily cinacalcet dosage administered was 0.99 mg/kg/day. Overall, 82% of patients on cinacalcet and 86% on placebo had ≥ 1 treatment-emergent adverse event; the most common were vomiting (32%, 24%, respectively), hypocalcemia (23%, 19%), nausea (18%, 14%), and hypertension (14%, 24%). - CONCLUSIONS: Despite early termination, efficacy and safety outcomes observed with cinacalcet in children with SHPT on dialysis were consistent with adult observations, suggesting cinacalcet may meet an unmet medical need for this population.